Automated, high‐throughput, in vivo analysis of visual function using the zebrafish. Issue 5 (6th March 2016) - Scott, C. Anthony; Marsden, Autumn N.; Slusarski, Diane C.
Abstract : Background: Modern genomics has enabled the identification of an unprecedented number of genetic variants, which in many cases are extremely rare, associated with blinding disorders. A significant challenge will be determining the pathophysiology of each new variant. The Zebrafish is an excellent model for the study of inherited diseases of the eye. By 5 days post‐fertilization (dpf), they have quantifiable behavioral responses to visual stimuli. However, visual behavior assays can take several hours to perform or can only be assessed one fish at a time.Results: To increase the throughput for vision assays, we used the Viewpoint Zebrabox to automate the visual startle response and created software, Visual Interrogation of Zebrafish Manipulations (VIZN), to automate data analysis. This process allows 96 Zebrafish larvae to be tested and resultant data to be analyzed in less than 35 minutes. We validated this system by disrupting function of a gene necessary for photoreceptor differentiation and observing decreased response to visual stimuli.Conclusions: This automated method along with VIZN allows rapid, high‐throughput, in vivo testing of Zebrafish's ability to respond to light/dark stimuli. This allows the rapid analysis of novel genes involved in visual function by morpholino, CRISPRS, or small‐molecule drug screens. Developmental Dynamics 245:605–613, 2016 . © 2016 Wiley Periodicals, Inc. Key findings: Automated the visual startle response in zebrafish. Created free software to instantaneously analyze the large spreadsheet of generated data. Creates opportunity for rapid, high‐throughput testing of novel genes which may be implicated in blinding disorders.